ANALISIS PESAN DAKWAH DALAM LIRIK LAGU SEBELUM CAHAYA KARYA BAND LETTO: Studi Analisis Semiotika Ferdinand De Saussure - Hadi Ismanto; Achmad Naufal Hanif Pasaribu (AN-NASHIHA Journal of Broadcasting and Islamic Communication Studies, 2023)
Islam is a religion that calls on its people to carry out da'wah, one of the da'wah carried out by the Letto band group is da'wah using music, at first glance the band's work is only limited to works about human romance with humans but if examined the song contains many da'wah messages, therefore. This research aims to: Knowing the results of the Analysis of the Song "Before Light" using Ferdinand de Saussure's Structural Semiotics Theory, as well as to find out the da'wah message contained. This research uses qualitative research. Researchers, using a structural semiotics analysis research approach according to Ferdinand de Saussure's theory, to dissect the meaning of the song "Sebelum Cahaya" by the band Letto. This structuralist semiotics thinks using symbols or signs as its starting point. Symbols or signs here are defined as writings or texts that have meaning. Based on the results of the analysis in the song Sebelum Cahaya. From the whole series, researchers get the results, 1) In this study, researchers used Ferdinan de Saussure's theory which has several concepts including parole and langue, signifier and signified, syntagmatic and paradigmatics. Parole and signifier are both in the form of the whole song lyrics before the light from beginning to end. Langue contains meanings in this study, among others, humans who are confused about pursuing dreams to ask God for help to guide them so they don't lose their way. The signifier describes a man who remembers his dreams and ideals that lead to not knowing the direction and purpose of his life. Syntagmatic there are 3 stanzas that are interconnected, the first stanza is a man who has lost his way, the second stanza is man's relationship with Allah, the third stanza is man as an object who asks for help from Allah. Paragdigmatics in this case there is a relationship between the words remembered and forgotten, accompanying, and leaving, as well as strength and weakness. 2) The type of da'wah message contained in the song Sebelum Cahaya contains da'wah messages: aqidah message discusses a human being who does dhikr from a form of faith in God, his morals message discusses a human being who tries istiqomah to carry out the teachings of Islam, his sharia message discusses a human being who loses direction but God will always accompany and invite his people to go to a better path.